Analisis Sentimen Pada Ulasan Produk UNIQLO dengan Algoritma Naive Bayes - Amelia, Eneng Elsa; Yustiana, Indra (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
Sentiment analysis is provided by internet users on social media to express personal assessments or opinions. One of the brands that often receives sentiment from users on social media is Uniqlo. Sentiment opinions play a crucial role. In the context of business and information technology, sentiment analysis is often applied to product reviews, customer service, or consumer responses on social media to gather information about how the public perceives a product or brand, which is valuable for both other customers and the store. Currently, the activity of providing product reviews, often referred to as reviews, is gaining attention from many parties and becoming a profession of choice. However, becoming a reviewer requires genuine experience and expertise in the field. This is because reviews, in the form of critiques and suggestions, must be conducted with careful consideration. Those who conduct reviews will adhere to the principles of analysis and facts rather than arbitrary opinions. Reviews, although in the form of concise summaries, can be very useful in various fields, from marketing to the arts. Reviews are a form of evaluation or assessment of a product, service, work of art, book, film, place, or anything else. It involves giving personal opinions or perspectives based on personal experience or knowledge of the subject being reviewed. Reviews can be positive, negative, or neutral depending on the experience, views, or individual perspectives of the reviewer. By using Text Mining classification methods, it is possible to determine whether a sentiment is positive, neutral, or negative. One widely used algorithm in sentiment analysis is the Naïve Bayes classification method.